Augmented futures?: scenarios and implications of augmented reality use in public spaces - Gudowsky, Niklas; Kowalski, Jacqueline; Bork-Hüffer, Tabea (Futures, 2023)
Expectations regarding augmented realities (AR) produce a range of anticipatory imaginations, ranging from hyperbolic visions to fears of entangled risks, negative effects and dystopian futures. On the one hand, assessing visions of emerging technologies brings to the fore the political economy of research and development of such technologies. On the other, developing plausible scenarios seeks to stimulate active socio-political negotiations regarding which futures are desirable (or not) and should (not) be pursued. AR technology may become a highly influential shaper of public spaces, and therefore the futures of humanistic and democratic societies. We introduce the methodology and results of an iterative survey-based scenario-building process, collecting highly interdisciplinary perspectives on augmented reality use in public spaces within the next decade. We outline four ‘extreme ends’ of plausible futures: ‘autocratic augmented reality’, ‘big-tech monopoly’, ‘DIY proliferation’ and ‘participatory public space’, concluding with a discussion of what effects these scenarios would have on societies, and a critical reflection on the scenario-building process and its limits.
Gesehen am 09.04.2025
Online veröffentlicht: 27. Mai 2023